DEVELOPING SUPPLEMENTARY READING MATERIALS FOR ISLAMIC LEARNERS OF MAN 03 MALANG BASED ON GENRE BASED APPROACH - Hanura Febriani (Linguists : Journal of Linguistics and Language Teaching, 2015)
Islamic schools/madrasah are expected to be source for students to have a good generaleducation based on the national curriculum plus a religious education designed to inculcate astrong understanding of religious and moral values based on the tenets of Islam. Englishteaching and learning process in MAN 03 Malang especially MAKBI (Madrasahaliyahkeagamaanbertaraf International) program encountered many problems in readingactivity since they were derived from religious program that is but they has less familiarity toEnglish Islamic reading material and only got general material in English. The main book thatused by the English teacher in teaching English has not attract students interest and provideless variety in teaching reading process with uninteresting illustration. Concerning theseproblems, a set of supplementary reading materials for the students needed to be developed.This materials using Genre based approach that is in line with the school curriculum. In thisresearch, the researcher employed the procedures: conducting need analysis, developingsupplementary materials, conducting expert validation, revising the materials, trying out thematerials, and revising the materials. The researcher collected the data by usingquestionnaires, interview, analyzing the syllabus, and note field. The product of this researchis three units of supplementary reading materials for eleventh year students of senior highschool at MAN 03 Malang, East Java.